Increasing the Economic Value of Hydrogel as an Alternative Planting Media at Madrasah Aliyah Swasta Muhammadiyah Sidomulyo - Hamid, Muhammadin; Simanjuntak, Crystina; Rianna, Martha; Amaturrahim, Suci Aisyah; Saragi, Indah Revita; Felly, Putri Aldika; Siahaan, Chyntia; Waruwu, Delima; Talanda, Aknes; Tambunan, Miranda (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2024)
Hydrogel technology can be used as a solution for indoor growing media. Hydrogel is a three-dimensional polymer network with cross-linked hydrophilic polymers, which are capable of swelling or storing water and physiological solutions up to thousands of times their dry weight, and are not easily soluble. To increase knowledge about ornamental plant cultivation using hydrogel media, a service was carried out by using partners at the Madrasah Aliyah Swasta Muhammadiyah Sidomulyo. This service aims to provide solutions to partners in the form of alternative hydrogel-based planting media made from alginate that are environmentally friendly which can be used as moisture and nutrient control agents. This goal is achieved through outreach activities, training, and the application of alternative planting media on ornamental plants. The target of the results to be achieved is to increase the economic value of hydrogels and to foster the entrepreneurial spirit of the students of Madrasah Aliyah Swasta Muhammadiyah Sidomulyo.